ANALISIS AKUNTANSI DANA INVESTASI ASURANSI UMUM SYARIAH DAN KONVENSIONAL SERTA PERLAKUAN TERHADAP HASIL INVESTASI (Studi Kasus Pada PT. Asuransi Asei Indonesia) - Muhammad, Reynaldi; Tinangon, Jantje J.; Runtu, Treesje (Universitas Sam Ratulangi, 2017)
This case study discusses the accounting treatment of investment funds from sharia and conventional insurance products at PT Asuransi Asei Indonesia. Thats matter supported by the differences in principles and standards governing the shariah and conventional insurance business. The purpose of this research is to know the activity of investment fund management conducted by PT. Asuransi Asei Indonesia on sharia and conventional insurance products. Data analysis method used in this research is descriptive, with qualitative approach. The results of the study reveal the application of accounting and revenue sharing of investment funds, in accordance with generally accepted accounting principles and standards, namely PSAK 108 for sharia insurance and PSAK 28 for conventional insurance. from the results of the research can be concluded that the placement of investment instruments by the company by following the PMK No.11/PMK.010/2011 and PMK No.53/PMK.010/2012 are in accordance with the principles and standards of sharia and conventional insurance. It is expected that the company remains obedient to regulated investment limits. And it is better to open a sharia link unit to really separate the sharia-based and conventional-based insurance business.Keywords: General Insurance, profit sharing, investment funds, PSAK 108